2023
DOI: 10.1111/jfd.13816
|View full text |Cite
|
Sign up to set email alerts
|

A specific and sensitive droplet digital polymerase chain reaction assay for the detection of tilapia lake virus in fish tissue and environmental samples

Abstract: Tilapia lake virus (TiLV) causes high mortality in farmed and wild tilapia in various countries. We developed a highly specific and sensitive droplet digital polymerase chain reaction (ddPCR) assay to detect and quantify TiLV. The ddPCR assay could detect the virus at a lower threshold than the reverse transcription‐quantitative polymerase reaction (RT‐qPCR) method, and the sensitivity of the ddPCR assay was 10‐fold higher. The diagnostic sensitivity and specificity of the ddPCR assay were 100% and did not cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Therefore, the LOD reported by those authors would be between the LOD values we observed with RGNNV (0.1 cps/rctn) and SJNNV (6.8 cps/rctn). Similar LOD values have been reported by other authors for infectious spleen and kidney necrosis virus (3 cps/rctn; [16]), carp edema virus (2.2 cps/rctn; [17]), largemouth bass ranavirus (2.0 cps/rctn; [18]) or tilapia lake virus (3.3 cps/rtcn; [19]). A lower LOD, 0.07 cps/µL, has been reported for a method developed for tilapia parvovirus [20]; assuming a volume of 2 µL of template per ddRNA reaction mixture, that LOD would be equivalent to 0.14 cps/rctn, quite similar to what we obtained for the RG type with our protocol.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the LOD reported by those authors would be between the LOD values we observed with RGNNV (0.1 cps/rctn) and SJNNV (6.8 cps/rctn). Similar LOD values have been reported by other authors for infectious spleen and kidney necrosis virus (3 cps/rctn; [16]), carp edema virus (2.2 cps/rctn; [17]), largemouth bass ranavirus (2.0 cps/rctn; [18]) or tilapia lake virus (3.3 cps/rtcn; [19]). A lower LOD, 0.07 cps/µL, has been reported for a method developed for tilapia parvovirus [20]; assuming a volume of 2 µL of template per ddRNA reaction mixture, that LOD would be equivalent to 0.14 cps/rctn, quite similar to what we obtained for the RG type with our protocol.…”
Section: Discussionsupporting
confidence: 89%